1973
DOI: 10.1083/jcb.58.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Dna Synthesis and Periodic Expression of Enzyme Activity in the Cell Cycle of Wi-38

Abstract: Synchronous cultures of WI-38 were obtained using an automated system for detachment and partitioning of mitotic cells which operates without the use of inhibitors, altered medium, or lowered temperatures . The generation time in synchronous WI-38 is 19 .5 h and the duration of S phase when determined from the percentage of labeled metaphase cells or nuclei is 12 h. DNA replication in WI-38 occurs in three temporally distinct and rapid bursts separated by intervals of greatly reduced synthesis within what is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…They do not agree with the report of Collins (1978) that diploid WT38 cells synt,hesize DNA (and incorporate 3H-TdR) maximally in early and late S-phase. In addition, we failed t,o detect significant, oscillations in 'H-TdR incorporation throughout S-phase as previously report,ed for diploid cells (Remington andKlevecz, 1973: Klevecz andKapp, 1973). These result,s are all consist,ent with the proposal by Klevecx (1969) t.hat true diploid cell strains incorporat,e 'H-TdR in two discrete parts of S-phase with a slowing in mid-S-phase while established heteroploid cell lines show a unimodal 'H-TdR incorporation curve.…”
Section: Ui Scussioncontrasting
confidence: 69%
“…They do not agree with the report of Collins (1978) that diploid WT38 cells synt,hesize DNA (and incorporate 3H-TdR) maximally in early and late S-phase. In addition, we failed t,o detect significant, oscillations in 'H-TdR incorporation throughout S-phase as previously report,ed for diploid cells (Remington andKlevecz, 1973: Klevecz andKapp, 1973). These result,s are all consist,ent with the proposal by Klevecx (1969) t.hat true diploid cell strains incorporat,e 'H-TdR in two discrete parts of S-phase with a slowing in mid-S-phase while established heteroploid cell lines show a unimodal 'H-TdR incorporation curve.…”
Section: Ui Scussioncontrasting
confidence: 69%
“…Furthermore, a number of authors have reported that the kinetics of (3H) thymidine incorporation into DNA of various synchronized cell populations is not characterized by a single peak [as would be expected if the starting time of replicon clusters was random (811, but that DNA content rather increases in a saltatory fashion (13,19,20,22,30). In some studies, the measured LI.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of some mammalian cells in culture, when synchronized, show trimodal kinetics for the rate of [ 3 H]-thymidine incorporation during S-phase. A small very early burst of DNA synthesis is followed by two larger bursts (Klevecz and Kapp, 1973;Klevecz, 1975;Holmquist et al, 1982). Between the two larger bursts, the rate of DNA synthesis slows appreciably (Brylawski et al, 2004).…”
Section: Facultative Heterochromatin Repression and Late Replicmentioning
confidence: 99%